Respostas

2013-04-09T20:22:04-03:00

a) 9x - 6x + 6 = 15

     3x = 15 - 6

     3x = 9

      x = 9/3

      x = 3

 

b) 15 - 5x = 2x - 8 + 15

     5x - 2x = - 8 + 15 - 15

     3x = - 8

     x = - 8/3

     x = - 2,6

 

c) 4x + 40 - 2x + 10 = 0

    4x - 2x = 0 - 40 - 10

     2x = - 50

     x = - 50/2

     x = - 25

 

d) 6x - 3 = - 2x - 6

     6x + 2x = - 6 + 3

     4x = - 3

      x = - 3/4

      x = - 0,75

 

e) 15 + 3x + 6 = -7x + 2x + 2

     3x + 7x -2x = 2 - 15 - 6

     8x = - 19

     x = - 19/8

     x = - 2,375